Compressive and Flexural Strength Behaviors of Metakaolin Based Geopolymer Mortars Manufactured by Different Procedures - Aygormez, Y.; Canpolat, Orhan; Mashhadani, M. M. A.; Uysal, M. (AMER INST PHYSICS, 2018)
Geopolymers nowadays represent one of the most effective environmental friendly alternatives to the conventional Portland cement bindings. Totally manufactured using wastes and by-product industrial materials, geopolymer binding systems achieve both goals of less greenhouse gas emissions and feasible use of waste materials. In this paper, metakaolin based geopolymer mortars were manufactured using different procedures and their flexural and compressive strength properties were investigated in to determine the most useful manufacturing process in terms of strength, energy saving and sustainability.
Keywords: ACTIVATED FLY-ASH; CURING TEMPERATURE; MOLAR RATIO; RESISTANCE; BINDERS; CEMENT; Science & Technology - Other Topics; Engineering; Physics